Nilai-nilai Karakter Hamba Tuhan Berdasarkan Surat Titus 1:5,8 - Lawolo, Aprianus; Aruan, Tiopan (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
In this increasingly advanced world, the role of pastors is crucial. They must be extra striving to shepherd their congregation. However, today there are more or less servants of God who actually live in sin. One of them is in the sin of sexual harassment. This will cause the congregation to find it very difficult to trust the current pastor. And this will actually affect the growth of their faith. To answer the above problems, the author uses a qualitative descriptive method with a literature study approach. The results of the study show that the pastor can carry out his duties well and with integrity by maintaining a wise, fair character, and also maintaining the holiness of his own life.